Spatio-Temporal Variations of Reference Evapotranspiration in Western Iran - Yasser Sabzevari; Saeid Eslamian (Indonesian Journal of Geography, 2023)
Optimal management of water resources requires accurate determination of water balance components in each region and Evapotranspiration is one of the most important components of water balance. The purpose of this study was to investigate the spatiotemporal variability of reference evapotranspiration in Lorestan province- western Iran country using the Man-Kendall test and GIS then assess the effect of different climatic parameters on ET0 using multivariate regression. Lorestan province with a 28064 km area in western Iran has 9 synoptic stations including Khorramabad, Boroujerd, Aligouderz, Azna, Doroud, Koohdasht, Poldokhter, Aleshatar, and Noorabad. In this study, meteorological data were used for 9 synoptic stations of the Lorestan in a period from 2001 to 2017. The results showed that at most of the stations and most months, the changing trend was decreasing. The annual decrease in Azna station with Z=-2.73 at 99% level, and in the stations of Aligodarz, Kohdasht, and Doroud with Z equal to -2.27, -2.35, and -2.2, respectively at 95% was significant. The spatial distribution of ET0 showed that the maximum amount of ET0 occurred in the south of Lorestan Province, and decreased from south to north and west to east of the study area. These results indicate the influence of latitude and altitude on the spatial distribution of ET0. The impact of different parameters showed the greatest effect of maximum temperature and wind speed on ET0.